Use of ocular hypotensive prostaglandin analogues in patients with uveitis: does their use increase anterior uveitis and cystoid macular oedema?. Issue 7 (6th May 2008) - Chang, J H; McCluskey, P; Missotten, T; Ferrante, P; Jalaludin, B; Lightman, S
Abstract : Aim: A retrospective comparative case series was studied to determine whether the use of prostaglandin (PG) analogues to treat raised intraocular pressure (IOP) in patients with uveitis resulted in an increase in the frequency of anterior uveitis or cystoid macular oedema (CMO). Methods: 163 eyes of 84 consecutive patients with uveitis and raised IOP treated with a PG analogue at two tertiary referral uveitis clinics were identified over a 3-month period. Control eyes were selected as those uveitic eyes of the same patients, which were treated with topical IOP-lowering agent(s) other than a PG analogue. Pretreatment IOP was compared with the mean IOP during PG analogue treatment. The frequency of anterior uveitis and CMO during PG analogue treatment was compared with the frequency of these complications in the control eyes during non-PG IOP-lowering treatment. Results: Significant IOP reductions were observed during PG analogue treatment. There was no significant difference in the frequency of anterior uveitis in those eyes treated with PG analogues and those treated with non-PG agents (p = 0.87, Fisher exact test). None of the 69 uveitic eyes without a previous history of CMO developed this complication. There was no increase in the frequency of visually significant CMO during PG treatment compared with that during non-PG treatment (p = 0.19, Fisher exact test). Conclusion: This study demonstrates that PG analogues are potent topical medications for lowering raised IOP in patients with uveitis and are not associated with increased risk of CMO or anterior uveitis.